2019
DOI: 10.1002/14651858.cd009786.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopy for diagnosing resectability of disease in women with advanced ovarian cancer

Abstract: High risk of bias 4 Applicability concerns * No studies reported outcome of surgery of no residual macroscopic disease and performed the reference standard in all women ** Only two studies performed the reference standard in all women, sensitivity and specificity are based on these two studies 1 Non of the studies performed the reference standard in test-positive women 2 Applicability concerns based on inclusion of not only women planned for primary debulking surgery or conventional diagnostic work-up not conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 64 publications
0
27
0
5
Order By: Relevance
“…A laparoscopy scoring system has been introduced, 26 but the most crucial areas for resectability may be difficult to access with laparoscopy, resulting in hidden areas of carcinomatosis, 27 making it less feasible. A recent Cochrane review 28 concluded that laparoscopy could be a useful tool for identifying women with nonresectable disease, but the reviewed studies included women who had incomplete surgery, with laparoscopy predicting total resectability. Moreover, in recent years, CRS has become more extensive, making evaluation with laparoscopy more difficult.…”
Section: -Specificitymentioning
confidence: 99%
“…A laparoscopy scoring system has been introduced, 26 but the most crucial areas for resectability may be difficult to access with laparoscopy, resulting in hidden areas of carcinomatosis, 27 making it less feasible. A recent Cochrane review 28 concluded that laparoscopy could be a useful tool for identifying women with nonresectable disease, but the reviewed studies included women who had incomplete surgery, with laparoscopy predicting total resectability. Moreover, in recent years, CRS has become more extensive, making evaluation with laparoscopy more difficult.…”
Section: -Specificitymentioning
confidence: 99%
“…A pooled analysis was not possible because of the heterogeneity of the data. Only two of the 18 studies included information on the false-positive rate, that is, laparoscopic assessment of suboptimal tumour reduction was followed by debulking surgery with resulting residual tumour ≤ 1 cm 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Eine gepoolte Analyse war aufgrund der Heterogenität der Daten nicht möglich. Angaben zur Falsch-positiv-Rate, d. h. nach laparoskopischer Einschätzung einer suboptimalen Tumorreduktion folgte eine Debulking-Operation mit resultierendem Tumorrest ≤ 1 cm, wiesen nur 2 der 18 Studien auf [37].…”
Section: Makroskopischer Tumorrest Vs Makroskopische Tumorfreiheitunclassified
“…Therefore, the selection of women who would benefit from PDS may be possible. However, due to the large heterogeneity of the included studies, careful interpretation of the study result is crucial (39). The laparoscopic criteria for the prediction of optimal debulking are summarized in Table 2.…”
Section: Diagnostic Laparoscopymentioning
confidence: 99%